Hubungan Impostor Phenomenon dan Career Decision-Making Difficulties dengan Psychological Resilience sebagai Mediator pada Mahasiswa Tingkat Akhir - Davina Veronica; Zamralita Zamralita; Ismoro Reza Prima (AHKAM, 2025)
Final-year university students often face academic pressure, social demands, and career uncertainty that can trigger the impostor phenomenon (IP) and increase career decision-making difficulties (CDMD), while low psychological resilience (PR) may further weaken their ability to make career decisions. This study aimed to examine the relationship between IP and CDMD, the relationship of PR with both variables, and the mediating role of PR in the relationship between IP and CDMD among final-year students in Indonesia. A quantitative approach with a cross-sectional correlational design was employed, involving 201 final-year students selected through purposive sampling. The instruments used were the Clance Impostor Phenomenon Scale (CIPS), the Career Decision-Making Difficulties Questionnaire (CDDQ), and the Connor–Davidson Resilience Scale (CD-RISC). Data were analyzed using SPSS and Jamovi through assumption testing, descriptive statistics, Spearman correlations, linear regression, and the Sobel test. The results showed that IP was positively and significantly associated with CDMD, while PR was negatively and significantly associated with CDMD, and no significant relationship was found between IP and PR. Nevertheless, PR was found to be a significant mediator in the relationship between IP and CDMD through an indirect effect. These findings indicate that IP increases difficulties in career decision-making, whereas PR functions as a protective factor that attenuates this effect. The study underscores the importance of resilience-based intervention programs within career counseling services to help final-year students cope more adaptively with self-doubt and career uncertainty.